Length of Stay Patterns and Their Relation to Coding Accuracy: Polanya Lama Tinggal Pasien dan Hubungannya dengan Akurasi Koding - Muchlis, Husni Abdul; Qomarania, Witri Zuama; Nurmalasari, Mieke; Kurniawati, Anastasia Cyntia Dewi; Lestari, Betri Widya (Universitas Muhammadiyah Sidoarjo, 2025)
Hospitals face efficiency and quality challenges within the Case-Based Groups (CBG's) financing system, where a patient’s Length of Stay (LOS) is critical. Accurate LOS data is crucial for strategic decisions, cost management, and quality care. A study at a Type B Hospital in Bekasi City found significant variation and outliers in LOS, indicating a non-normal distribution. This observational analytic study, involving 3,151 inpatient claims from January 2024, analyzed LOS data and its impact on clinical documentation and coding quality. The analysis compared the Arithmetic Mean Length of Stay (AMLOS) and the Geometric Mean Length of Stay (GMLOS) to identify outliers, followed by a Wilcoxon test. Results showed LOS varied from 1 to 48 days, with an AMLOS of 7.13 and a GMLOS of 6.76 days, indicating positive skewness from outliers. AMLOS was consistently higher than GMLOS in the top 10 CBG's, especially for moderate and severe cases. The Wilcoxon test (p<0.05) confirmed a significant statistical difference, showing GMLOS more accurately represents the appropriate LOS. The presence of outliers (e.g., >30 or 44 days) suggests potential issues with documentation or coding. Therefore, using the more robust GMLOS is crucial for hospitals to optimize management, improve care, and maintain the quality of clinical documentation and coding.